2013
DOI: 10.2196/jmir.2277
|View full text |Cite
|
Sign up to set email alerts
|

Engagement Promotes Abstinence in a Web-based Cessation Intervention: Cohort Study

Abstract: BackgroundWeb-based smoking cessation interventions can have a public health impact because they are both effective in promoting cessation and can reach large numbers of smokers in a cost-efficient manner. Their potential impact, however, has not been realized. It is still unclear how such interventions promote cessation, who benefits most, and how to improve their population impact.ObjectiveTo examine the effectiveness of a highly promoted Web-based smoking cessation intervention to promote quit behavior over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 51 publications
(61 reference statements)
5
97
1
Order By: Relevance
“…As mentioned previously, many participants failed to view the intervention, highlighting the importance of tracking and reporting program exposure in studies testing the effectiveness of online interventions. Additionally, follow-up retention rates were lower than ideal (68.6% at 2 months, 63.3% at 6 months, and 72.4% at 12 months) but higher than reported in other recent online smoking intervention studies (Pike, Rabius, McAlister, & Geiger, 2007;Richardson et al, 2013;Smit, Hoving, Cox, & de Vries, 2012;Stoddard, Augustson, & Moser, 2008;Swartz et al, 2006). This did not impact our treatment utilization outcomes, but it could have resulted in lower abstinence rates than actually occurred among participants because missing participants were counted as smokers.…”
Section: Discussionmentioning
confidence: 57%
“…As mentioned previously, many participants failed to view the intervention, highlighting the importance of tracking and reporting program exposure in studies testing the effectiveness of online interventions. Additionally, follow-up retention rates were lower than ideal (68.6% at 2 months, 63.3% at 6 months, and 72.4% at 12 months) but higher than reported in other recent online smoking intervention studies (Pike, Rabius, McAlister, & Geiger, 2007;Richardson et al, 2013;Smit, Hoving, Cox, & de Vries, 2012;Stoddard, Augustson, & Moser, 2008;Swartz et al, 2006). This did not impact our treatment utilization outcomes, but it could have resulted in lower abstinence rates than actually occurred among participants because missing participants were counted as smokers.…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, the importance of logins is consistent with other trials that have identified Web site utilization as an independent predictor of abstinence. 18,[44][45][46] Increasing Web site utilization and improving adherence to the core components of web-based interventions are a priority not only for smoking cessation programs but also for eHealth interventions broadly. [47][48][49] Hypotheses regarding moderator variables were only partially supported.…”
Section: Discussionmentioning
confidence: 99%
“…Though a recent paper has found no direct benefit of using a values clarification tool for heart disease-related decision making [43], several recent studies in cancer-related decision making have found that both breast cancer and PCa patients have better outcomes, such as less decisional conflict, when using media with interactive elements versus informational materials with no interactivity [28,[31][32][33]. Additionally, a recent paper assessing participants' use of a web-based smoking cessation tool found that increased use of interactive website features and more frequent use of the website contributed to sustained smoking cessation [34]. Increased interactivity may play a key role in using the Internet to improve decision-making outcomes [20], such as expanding the use of a values clarification tool or expanding opportunities for patients to provide feedback throughout the website [44], such as brief quizzes about PCa facts.…”
Section: Original Researchmentioning
confidence: 99%
“…Tracking software captured website use, allowing for an investigation of whether use of informational sections, testimonial videos, and the values clarification tool were associated with decisional outcomes. Based on prior studies in several domains [14,28,[31][32][33][34] and on a model of Internet interventions [14], we hypothesized that greater interaction with the website would be associated with improved knowledge and satisfaction, decreased decisional conflict, and decreased screening rates.…”
Section: Introductionmentioning
confidence: 99%